Compliance with the north American Society of Pacing and Electrophysiology guidelines on amiodarone monitoring in Riyadh, Saudi Arabia: a retrospective charts review study - Bander Ahmed Albassam; Nouf Mohammed Almutairi; Sarah Fahad Aldosari; Hind Saleh Almodaimegh (Taylor & Francis Group, 2020)
Background Amiodarone is known for its efficacy as an antiarrhythmic agent; however, its extensive side-effect profile requires careful selection of patients and frequent monitoring. The purpose of this study was to evaluate the performance of the baseline tests before initiating amiodarone therapy and the on-going monitoring based on the North American Society of Pacing and Electrophysiology guidelines recommendations. Methods A retrospective descriptive charts review study included all patients who are 18 years of age and older and were started on oral amiodarone with a primary diagnosis of any type of cardiac arrhythmia from January 2016 to December 2018 in King Abdualziz Medical City, Riyadh, Saudi Arabia. The medical charts were reviewed and evaluated based on the performance of the recommended baseline and follow-up of chest X-ray (CXR), liver function test (LFT), thyroid function test (TFT) and electrocardiogram (ECG). The continuous variables were analyzed and presented as mean ± SD and the categorical variables were presented as percentages. Results Over the study period, 143 eligible participants on amiodarone therapy were included, with an average of 165 ± 207 days on amiodarone. Of patients, 36.4% had the entire recommended baseline assessments before initiating amiodarone. Our results indicated optimal compliance rates to the baseline tests of CXR (79.7%), LFT (79.7%) and ECG (86.7%). However, there was a lower compliance rate to TFT recommendations (40.6%). The compliance rate to the guideline recommendations related to the follow-up tests was minimal. On-going monitoring performance rates were 47.6% of CXR, 49% of LFT, 54.5% of ECG and 22.4% of TFT. Conclusion The compliance with the guideline recommendations related to amiodarone baseline assessments was optimal for all the baseline tests, except for TFT. However, the proportion of patients who received all the recommended baseline assessments was minimal. In addition, the performance of on-going monitoring was suboptimal for all the follow-up tests. Improvements could be made by establishing a local protocol for amiodarone monitoring and pharmacists participating in amiodarone therapy assessments.